2016
DOI: 10.1007/s12011-016-0746-8
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Serum Trace Elements (Zn, Cu, and Fe) in Pakistani Patients with Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is a chronic autoimmune inflammatory disease, which mainly involves the joints. RA is prevalent worldwide with increasing prevalence in elderly people. The mechanism of RA pathogenesis is still undefined, and it is interplaying between genetic susceptibility and environmental factors. Although risk factors for RA are not fully established, various studies have focused on the role of trace elements in association with RA. Trace elements act as co-factors for most of the enzymes, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Our data oscillate between − 0.03 and − 0.12 in the urban population and − 0.36 in the rural population in the FN similarly with date from knee joint (Roczniak et al 2017). There was a negative correlation of Zn/Cu in the blood of patients with diabetes and rheumatoid arthritis (Badran et al 2016;Ullah et al 2017). An imbalance of Zn/Cu content is linked with diabetes and diabetic complications (Hamasaki .…”
Section: Oxidative Stress Process and Fe And Cu Supplementationmentioning
confidence: 98%
“…Our data oscillate between − 0.03 and − 0.12 in the urban population and − 0.36 in the rural population in the FN similarly with date from knee joint (Roczniak et al 2017). There was a negative correlation of Zn/Cu in the blood of patients with diabetes and rheumatoid arthritis (Badran et al 2016;Ullah et al 2017). An imbalance of Zn/Cu content is linked with diabetes and diabetic complications (Hamasaki .…”
Section: Oxidative Stress Process and Fe And Cu Supplementationmentioning
confidence: 98%
“…The evaluations of Zn status in RA patients are scarce and few studies have used more than one biomarker, which could explain the controversial results (Mierzecki et al, 2011; Sahebari et al, 2016; Silverio Amancio et al, 2003; Ullah et al, 2017). In the present study, Zn intake was significantly lower for RA patients in comparison to healthy participants.…”
Section: Discussionmentioning
confidence: 99%
“…Among many risk factors, minerals and trace elements disorders have been recognized as risk factors of RA. 3,5,9 Previous studies reported chronic inflammation induced marked systemic alteration in blood mineral levels causing pathogenesis in RA patients. [1][2][3]5,[9][10][11][12][13] In addition to joints, RA adversely affects all the organ and system of the body and cardiovascular morbidity and mortality is well marked in RA patients.…”
Section: Introductionmentioning
confidence: 99%
“…3,5,9 Previous studies reported chronic inflammation induced marked systemic alteration in blood mineral levels causing pathogenesis in RA patients. [1][2][3]5,[9][10][11][12][13] In addition to joints, RA adversely affects all the organ and system of the body and cardiovascular morbidity and mortality is well marked in RA patients. [14][15] As because, cardiovascular involvement is silent, more than 40% of the premature deaths occur in RA due to cardiovascular diseases (CVD) 16 Analysis of HRV has been emerged as most reliable and non-invasive method for assessment of cardiac autonomic activity and reduced HRV is a marker of autonomic imbalance, which is a strong predictor of sudden cardiac death.…”
Section: Introductionmentioning
confidence: 99%